2015
DOI: 10.1007/s00041-015-9408-z
|View full text |Cite
|
Sign up to set email alerts
|

Frame Potentials and the Geometry of Frames

Abstract: This paper concerns the geometric structure of optimizers for frame potentials. We consider finite, real or complex frames and rotation or unitarily invariant potentials, and mostly specialize to Parseval frames, meaning the frame potential to be optimized is a function on the manifold of Gram matrices belonging to finite Parseval frames. Next to the known classes of equal-norm and equiangular Parseval frames, we introduce equidistributed Parseval frames, which are more general than the equiangular type but ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…This paper is dedicated to the construction of other types of OGFs. By examining the behavior of the gradient descent for a frame potential that is a smooth perturbation of µ(F) [5], we discovered the following OGF in Ω 5,2 .…”
Section: Definition Two Unit-norm Tight Framesmentioning
confidence: 99%
“…This paper is dedicated to the construction of other types of OGFs. By examining the behavior of the gradient descent for a frame potential that is a smooth perturbation of µ(F) [5], we discovered the following OGF in Ω 5,2 .…”
Section: Definition Two Unit-norm Tight Framesmentioning
confidence: 99%
“…which has been studied in several works including Welch [67], Conway et al [31], Strohmer and Heath [62], and more recently [40,9]. The problem (1.3) is often referred as the best line-packing problem because it asks how to arrange N lines in H d so that they are as far apart as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Significant interest in FUNTFs started in 2003 when Benedetto and Fickus proved that for every k ≥ n, every n-dimensional Hilbert space has a FUNTF of k vectors [BF03]. To do this they defined a positive function on the set {(x j ) k j=1 : x j ∈ H, x j = 1}, called the frame potential, so that a collection of vectors minimizes the frame potential if and only if the vectors form a tight frame for H. Since then, researchers have been interested in understanding the geometry and topology of FUNTFs [BH15] [CMS17] and properties of the frame potential itself [FJKO05] [JO08]. In [DFKLOW04], an algorithm is given to create FUNTFs and in [CF09] it is shown that the method of gradient descent on the frame potential can be used to create FUNTFs.…”
Section: Introductionmentioning
confidence: 99%